Characterization of buffalo bull frozen-thawed sperm proteins through SDSPAGE and their correlation with HOST and in vitro acrosome reaction - SINGH, A K; BRAR, P S; CHEEMA, RANJNA S; KAUR, M; BANSAL, A K (The Indian Journal of Animal Sciences, 2014)
Intrinsic factors such as proteins modulate the fertilizing ability of male gametes. The present study was undertaken to separate and compare the protein of sperm SDS-extracts from 30 bulls by SDS-PAGE and correlate quantity of various proteins with hypo-osmotic swelling test (HOST) and acrosome reaction. There were 26 major polypeptides, ranging from 12–23 proteins in each semen sample. These bands were separated in the range of 18–345 kDa in frozen-thawed semen by SDS-PAGE on 10% acrylamide gel with bands 135, 110, 48, 41, 37, 31, 28, 26, 24, 20 and 18 kDa present in all the tested frozen semen. There were positive correlations between 5 protein bands 135, 70, 55, 26 and 18 kDa and HOS positive (r2 = 0.28, r2 = 0.19, r2 = 0.37, r2 = 0.24and r2 = 0.31, respectively) and acrosome reacted spermatozoa (r2 = 0.29, r2 = 0.38, r2 = 0.42, r2 = 0.32 and r2 = 0.14, respectively). Both qualitative (presence or absence of bands) and quantitative differences (concentration of protein in each amplified band) were observed in fertility associated protein bands. The concentration of fertility associated proteins was relatively higher in sperm extracts of buffalo bulls having > 60% HOS positive and > 50% acrosome reacted spermatozoa than in their counterparts.The concentration of proteins 55 kDa (30.7 ± 6.0 μg/band) and 26 kDa (22.1 ± 2.5 μg/ band) was highest of all the protein bands identified through SDS-PAGE using 10% separating gel and 4% stacking gel and were linked to the osteopontin and lipocalin-type prostaglandin D synthetase subunits, respectively, of the bovine semen. HOST and in vitro acrosome reaction were indicators of fertility, and therefore, proteins of 55, 31, 26, 24, 20 and 18 kDa may be candidates for protein fertility markers in buffalo bull spermatozoa. In conclusion, 26 proteins were identified in frozen sperm extracts and significantly correlated with HOST and acrosome reaction.